Petisi Indonesia untuk Dunia: Potret Globalisasi Gerakan Sosial Digital - Andreas Ryan Sanjaya (Fakultas Ilmu Komunikasi Universitas Tarumanagara, 2018)
Internet technology brought out about changes in human life. The apparent changes in this study lied in two respects. First, changes in the way citizens conduct social movements. Second, the internet reinforces the impact of globalization, so the issues raised by citizens are also a global issue. This study revealed a portrait of globalization in the digital social movement in Indonesia. The selected case is an online petition addressed to international parties for genocide in Myanmar. The analytical approach in this study used social semiotics. The three components analyzed were field of discourse, tenor of discourse, and mode of discourse. The result was a petitioner used international criminal issues, as well as provocative terms to reinforce the message in the text. Teknologi Internet membawa perubahan pada kehidupan manusia. Perubahan yang tampak dalam penelitian ini terletak pada dua hal. Pertama, perubahan pada cara warga melakukan pergerakan sosial. Kedua, internet menguatkan pengaruh globalisasi, maka isu-isu yang diangkat oleh warga juga merupakan isu global. Penelitian ini mengungkap potret globalisasi dalam gerakan sosial digital di Indonesia. Kasus yang dipilih adalah petisi online yang ditujukan kepada pihak internasional atas kasus genosida di Myanmar. Pendekatan analisis dalam penelitian ini menggunakan semiotika sosial. Tiga komponen yang dianalisis adalah medan wacana, pelibat wacana, dan sarana wacana. Hasilnya adalah pembuat petisi menggunakan isu-isu kejahatan internasional, serta istilah-istilah provokatif untuk menguatkan pesan dalam teks.